The level of tolerance for political belligerents among household heads in Lawaan, Eastern Samar. - Gonzaga, Angelyn (Angelyn Gonzaga [and] Ma. Bernadette T. Inciso, 2010)
This research study is centered on the municipality of Lawaan, eastern Samar. It has sixteen barangays all in all, comprising a total population of 11, 302. Lawaan lies between the municipalities of Marabut, Samar and Balangiga, Eastern Samar. Moreover, it faces the Lawaan Bay but is mountainous at the same time.